2015
DOI: 10.1007/s12032-015-0723-7
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression of galectin-3 and CRIP-1 in endometrial cancer: prognostic value and patient survival

Abstract: Endometrial cancer is the sixth most common cancer in women. Galectin-3 (GAL-3) and CRIP-1 are multifunctional proteins which seem to be involved in many neoplasias. This study aims to point out correlations between clinicopathological findings and endometrial cancer patient survival to GAL-3 and CRIP-1 expression in order to enfold their diagnostic/prognostic potential. Tissues from 46 patients diagnosed with endometrial cancer were studied by immunohistochemistry, using monoclonal antibodies for GAL-3 and CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…A few studies suggest that CRIP1 functions as an oncogene. Lambropoulou et al showed that higher expression of CRIP1 is associated with shorter survival times in endometrial cancer [22]. Our data supports the oncogenic role of CRIP1.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A few studies suggest that CRIP1 functions as an oncogene. Lambropoulou et al showed that higher expression of CRIP1 is associated with shorter survival times in endometrial cancer [22]. Our data supports the oncogenic role of CRIP1.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have indicated that CRIP1 is involved in few types of cancers, including osteosarcoma [19], breast cancer [20], endometrial cancer, [22] and prostate cancer [17]. However, the role of CRIP1 is not conclusively reported in these cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cysteine-rich intestinal protein 1 (CRIP1) belongs to the LIM/double-zinc finger protein family and has been shown to be overexpressed in several tumor types, including breast, endometrial and prostate (45,49,50).…”
Section: Dna Methylation and Prostate Cancermentioning
confidence: 99%
“…Furthermore, the cell-cell and cell-matrix interactions exhibited by galectins and their high affinity for specific oligosaccharides make galectins promising markers and/or therapeutic targets for cancer (8). The expression and function of galectins in EC prognosis and progression have not been well investigated to date, although galectin-3 production in epithelial cancer cells is significantly associated with poor prognosis and reduced survival rates 5 years after diagnosis (9). Galectin-7 is a 15 kDa prototype galectin expressed specifically by stratified epithelial cells (8).…”
Section: Introductionmentioning
confidence: 99%